Utilización de gramíneas y leguminosas para la producción del ganado bovino sostenible en el litoral ecuatoriano - Villacis Alban, Jeniffer Morelia (2019)
Grass grasses and legumes are the main food source for both domestic and wild herbivores as they grow spontaneously in most pastures. They have an easy adaptability to the varieties of climate that exist within the Ecuadorian coast, they contribute the highest percentage of dry matter and carbohydrates consumed by the animal, and at the same time they act as soil improvers. The production of grasses and legumes on the Ecuadorian coast is being maximized due to the fact that farmers start to implement new ideas to improve the feeding of cattle and as a result improve the production of either milk or meat.